INOVASI ALAT BIOREAKTOR DENGAN SISTEM FLUIDISASI DALAM PEMBUATAN ETANOL DARI MOLASSES - Amsar Amsar; Wahyu Diah Proborini; Fenny Suryanti (Reka Buana : Jurnal Ilmiah Teknik Sipil dan Teknik Kimia, 2016)
The fermentation process is generally carried out in the community is in a batch, but the process is the concentration of ethanol produced is quite low because of accumulated ethanol production will poison the microorganisms in the fermentation process. Ethanol productivity of batch processes is very small because it takes a long time of about 72 hours. High and low ethanol content is determined in part by sugar levels in the substrate. Sugar compounds are required as a carbon source of energy yeasts. This study aims to determine the maximum results from the opening of flow rate and flow of glucose concentration on the effectiveness of the process and the quality of ethanol. The method used is fluidized semikontinyu fermentation system using Saccharomyces cerevisiae immobilized with the order. The results showed that the fermentation process fluidization semikontinyu that teramobilisasi with that carried out during the first day with a sugar concentration of 15%, 20%, 25%, 30% derived ethanol content of 5%, 8%, 13%, 15% at a flow rate of 30 openings °. Ethanol is also obtained by 8%, 12%, 18%, 20% in opening a flow rate of 60°. Ethanol is also obtained by 8%, 13%, 19%, 21% in opening a flow rate of 90°.